(untitled) (Nigerian Journal of Physiological Sciences, 2021)
The hyperglycaemia of diabetes mellitus (DM) induces oxidative stress which damages the tissues. Glibenclamide, an oral hypoglycaemic drug used in the treatment of DM has associated side effects. Natural products are considered safe in the treatment of chronic diseases. Hibiscus sabdariffa (HS) is a plant that has demonstrated antidiabetic activity. We aimed to determine the potential benefits of co-administration of HS and glibenclamide in ameliorating oxidative stress in streptozotocin (STZ)-induced diabetic rats. A total of 25 male albino Wistar rats were divided randomly into five groups: control (Non-DM), diabetic (DM), diabetic treated with 600µg/kg BW of glibenclamide (DM + GLIB), diabetic treated with 500mg/kg BW of HS (DM + HS), diabetic treated with both 600µg/kg BW of glibenclamide and 500mg/kg BW of HS (DM + GLIB + HS). The interventions were administered for a period of 28 days. The Non-DM rats were significantly heavier (p<0.01) compared to rats in the other treatment groups. Glibenclamide or HS alone and in combination, significantly lowered (p < 0.001) the final fasting blood glucose concentration of the rats in the respective treatment groups. HS and a combination of HS+ GLIB resulted in increased (p<0.05) serum activity of catalase, glutathione peroxidase and superoxide dismutase compared to the DM untreated rats. The serum level of malondialdehyde was significantly lowered (p=0.000) in rats that received a combination of HS + GLIB compared to the DM untreated rats. Coadministration of HS + GLIB showed beneficial regeneration of islet-cells in the pancreas. Co-administration of HS + GLIB appears to be more beneficial in the treatment of DM and associated oxidative stress than when given as single agents. Thus, a case for their incorporation as a combined therapy for DM should be considered.